1993
DOI: 10.1121/1.408140
|View full text |Cite
|
Sign up to set email alerts
|

A clarification of nonexistence problems with the superposition method

Abstract: The purpose of this paper is to clarify the question of nonexistence of solutions for the superposition method in acoustic radiation and scattering problems. Recently a number of authors have implemented this method and have claimed that nonexistence or nonuniqueness difficulties do not arise. Numerical evidence appears to support this view. However, this paper shows that the superposition method is a discrete approximation to an equation that does suffer from nonexistence of its solution at certain frequencie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…10 As a remedy to this, we consider another set of point sources, s m,2 displaced inward from the sphere's surface by d 2 ¼ 0.0072 m. Then we consider the composite Green's functions of the form s m ¼ ð1 þ 1000i=kÞ s m;1 þ ð1 À 1000i=kÞ s m;2 :…”
Section: Numerical Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…10 As a remedy to this, we consider another set of point sources, s m,2 displaced inward from the sphere's surface by d 2 ¼ 0.0072 m. Then we consider the composite Green's functions of the form s m ¼ ð1 þ 1000i=kÞ s m;1 þ ð1 À 1000i=kÞ s m;2 :…”
Section: Numerical Examplesmentioning
confidence: 99%
“…In this paper, we use the method of virtual sources or wavefield superposition. [9][10][11] A set of 301 point sources of the form S 1 ðr; z; h : r 0 ; z 0 ; h 0 Þ ¼ À 1 4p…”
Section: Numerical Examplesmentioning
confidence: 99%
“…Although the formulations circumvent the singularity presented in the integral equation in BEM, it does surfer from the problem of non-uniqueness of solutions at some critical wave numbers [2] . By combining the single-layer and double-layer with a complex constant α, the hybrid-layer potential integral formulations were produced to solve the non-uniqueness problem.…”
Section: Theoretical Formulationmentioning
confidence: 99%
“…However, the resolution of the nonuniqueness problem in the WSM was questioned by other researchers. For example Wilton et al 52 and Leblanc et al 53 presented that the WSM is not free of the nonuniqueness problem and they showed that the nonuniqueness problem still exists at critical frequencies. Ochmann 7 also discussed that the nonuniqueness problem occurs in the WSM if the inner surface is closed.…”
Section: Wave Superposition Methodsmentioning
confidence: 99%